Innovative Solutions in Banking Offers – The Importance of Mobile Banking Applications in Bank Management - Sylwia STACHERA-WLODARCZYK (Communications of International Proceedings, 2021)
The objective of the publication is to present the main directions of changes in the area of banking innovation and to assess the potential, functionality and use of mobile banking solutions as an instrument supporting the development of banks. The subject of the study covered in particular mobile banking applications. The data necessary to conduct the analysis was obtained both from financial reports of selected financial institutions and from studies of internet portals. The obtained research results emphasized the importance of the banks' use of mobile banking products in their banking offer. Nowadays, ensuring convenient and modern ways of carrying out transactions, and thus customer satisfaction, is an important factor that preconditions banks to maintain a high level of competitiveness on the mobile banking services market.
Keywords: Innovations; Banking Innovations; Mobile Banking; Mobile Banking Applications